Pulmonary Hilar Tumor: An Unusual Presentation of Sclerosing Hemangioma - Jui-Hung Hung; Ching Hsueh; Chiung-Ying Liao; Shang-Yun Ho; Yuan-Chun Huang (Case Reports in Medicine)
Pulmonary sclerosing hemangioma is an uncommon benign tumor of the lung; however, on rare occasions it can arise from the pulmonary hilar region. Herein, we report a 53-year-old female patient who presented with a round opacity in the right upper lung field on a radiograph. Chest computed tomography scanning revealed a 3.1 cm mass in the right pulmonary hilum. Thoracoscopic tumor excision was subsequently performed. On pathohistologic study, the tumor was well defined and composed of round stromal cells and surface cells arranged in a papillary, sclerotic, solid, and hemorrhagic pattern. In immunochemical study, the round cells were positive for thyroid transcription factor-1 (TTF-1) and epithelial membrane antigen (EMA) and negative for cytokeratin. The surface cells were positive for TTF-1, EMA, and cytokeratin. Therefore, a final diagnosis of sclerosing hemangioma was confirmed. In conclusion, pulmonary sclerosing hemangioma is uncommon and rare in the pulmonary hilar region. CT scanning is useful to determine its benignity, although imaging features are not specific for a definite differential diagnosis from other pulmonary tumors. Therefore, tissue diagnosis is usually necessary, and pulmonary sclerosing hemangioma should be listed in the differential diagnoses of pulmonary hilar tumors.